Case Report: A Rare Case of Glioblastoma in Patient with HIV-AIDS - Ilham Munandar; M. Vitanata Arfijanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Patients with HIV_AIDS have an increased risk to develop neurological disorders include a complicationof intracerebral mass. Primary CNS tumors in this condition are rare and difficult to diagnose because it hasuncommon presentation, unusual tumor growth and manifests at a young age in a patient with HIV-AIDS.Advanced imaging techniques with contrast-enhanced magnetic resonance scans should be used to guidediagnosis in this condition. in a patient with HIV-AIDS, biopsy should be carried out if standard imagingshowed atypical features or in a patient who has a poor response to empirical treatment for neurotoxoplasmosis.In this case, we reported a case of A 26 years old male with HIV-AIDS with neurological deficits who laterdiagnosed with glioblastoma.